Aplicación web para la gestión de contenidos digitales e información de la Secretaría General de la Universidad Técnica de Cotopaxi. - Sailema Curicho, Janeth Maribel (2018)
The present technological proposal deals with the development of a web application for managing digital contents and information. The same will allow to manage the documents of the General Secretariat of the Technical University of Cotopaxi, such as: Resolutions of the Honorable University Council UTC, Historical Memory and Legal Norms. This project arose from the need to improve the processes carried out at this unit. In addition, it was observed that the documents were stored in physical format, which prevents searching and classifying the information efficiently. This caused a time and resources losing in the tasks that are developed in the General Secretariat. Therefore, the need for a web application that will improve these processes was evidenced. At the development of the application, the Iterative-Incremental Method was used because it fits the needs of the system, allowing the construction of a structured application according to the user's requirements. The tools used at this project were: Visual Studio 2015 and SQL Server 2012 Database. Finally, a computerized content management tool was developed to manage, search and download documents in a practical way. On the other hand, it allows that the General Secretariat to have a database of documentation of importance for the institutional life of the UTC. The web application will serve as a platform to disseminate information from this department to teachers, students, administrative and service personnel, as well as those people who require access to public information.